2018
DOI: 10.1007/s00267-018-1090-x
|View full text |Cite
|
Sign up to set email alerts
|

Windbreak Efficiency in Agricultural Landscape of the Central Europe: Multiple Approaches to Wind Erosion Control

Abstract: Windbreak is one of the key factors for making the agriculture systems successful through reduced wind erosion, improved microclimate, increased biodiversity, and production potentiality of timber and agricultural crops. Even though windbreak occupies only a small part of agricultural landscape, its advantages on the ecological and economical perspective are quite high. This study evaluated the effects of three windbreak types on the wind erosion control in relation to their structural diversities, wind-speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The most significant effect on the wind speed reduction in terms of structural indices was found in the total diversity index and Arten-profile index describing vertical structures, which are recommended, along with the optical porosity, to be evaluated in assessing the windbreak efficiency in controlling wind erosion [28]. Other authors deal with the effect of windbreaks on the surrounding microclimate, finding it favourable for both field crops and the effects on humidity and temperature of the surrounding air and soil [5,29,30]. The appearance and function of windbreaks are positively impacted by selecting a mix of conifers and deciduous trees and shrubs [31].…”
Section: Introductionmentioning
confidence: 99%
“…The most significant effect on the wind speed reduction in terms of structural indices was found in the total diversity index and Arten-profile index describing vertical structures, which are recommended, along with the optical porosity, to be evaluated in assessing the windbreak efficiency in controlling wind erosion [28]. Other authors deal with the effect of windbreaks on the surrounding microclimate, finding it favourable for both field crops and the effects on humidity and temperature of the surrounding air and soil [5,29,30]. The appearance and function of windbreaks are positively impacted by selecting a mix of conifers and deciduous trees and shrubs [31].…”
Section: Introductionmentioning
confidence: 99%
“…Non-shelterbelt forests (e.g., water and soil conservation forests and sand stabilization forests) play an important role in preventing water and soil erosion by intercepting rainfall by the canopy, reducing splash by litter and the understory, and limiting soil particle movement by the root systems (Zhao et al 2015) and controlling desertification by reducing wind erosion (Wang 2004;Vacek et al 2018). Most studies show that the canopy could intercept 10-40% of gross rainfall (Miralles et al 2010;Li et al 2017), which is influenced not only by rainfall events but also by the OSP, vegetation types, stand composition, and stand age.…”
Section: Quantitative Structures Of Non-shelterbelt Forests and Relatmentioning
confidence: 99%
“…For example, canopy interception loss of water and soil conservation forests decreased with increasing the OSP (Limousin et al 2008;Park and Cameron 2008), and natural vegetation has a gradually increased effect on water and soil conservation from natural grasslands to shrubs and trees (Zhao et al 2015). In addition, wind erosion control by sand stabilization forests was influenced by vegetation coverage, structure, and distribution pattern (Vacek et al 2018). Several studies showed that vegetation coverage above a certain threshold could protect surface soil, reduce wind speeds, and thus prevent dust entrainment and transport in the process of wind erosion (Huang et al 2001;Amichev et al 2015).…”
Section: Quantitative Structures Of Non-shelterbelt Forests and Relatmentioning
confidence: 99%
“…This was done by measuring wind speed for different distances before the fenders, and after the fenders, a station was set as a source of control. The results of the experiment showed that the height and porosity of the fenders play an important and influential role in reducing the wind speed (Vacek et al, 2018).…”
Section: Introductionmentioning
confidence: 99%